The ten commandments of professionalism for teachers : wisdom from a veteran teacher - Gill, Vickie (Thousand Oaks, Calif. Corwin Press, 2005)
Vickie Gill uses humour, stories, and personal experiences to convey the importance of professionalism in such areas as dealing with students and parents, being a role model, avoiding gossip, working with other teachers and school staff, after hours job duties and paperwork.
Keywords: Effective teaching; Teachers -- Training of